Frecuencia de consumo de bebidas alcohólicas ¿entre los pacientes con cáncer bucal de la unidad de cirugía maxilofacial y estomatología del HUSVP (Medellín) entre enero de 1996 y junio de 2000 - Restrepo-Ospina, Diana Patricia; Correa-Arenas, Carlos Andrés; Martínez, Carlos Enrique; Álvarez-Gómez, Gloria J.; Molina-Saldarriaga, Hernando (Revista Facultad de Odontología Universidad de Antioquia, 2020)
There are many risk factors associated with the appearance of oral cancer, among them are the cigarette and alcohol consumption. This descriptive retroprospective study measured different variables as age, sex, alcoholic drinks and cigarette consumption among patients with diagnosis of oral cancer at the Maxillofacial Surgery and Stomatology Service from the "Hospital Universitario San Vicente de Paul" in Medellin, Colombia. there was a high prevalence of oral cancer in men over 45 years, with a significant increase after the 60 years, being squamous cell carcinoma the main type of cancer diagnosed (88%). The most frequent location was the lateral border of the tongue. 36% of the patients were simultaneously alcohol and cigarette consumers and only 23% were pure alcoholic consumers. It was not possible to establish cause-effect relationship between alcohol consumption and oral cancer, although it was observed that there is a high risk when cigarette and alcohol are consumed simultaneously. It should be investigated another type of habits that could be associated to the appearance of oral cancer in our population, due to the high number of people with the illness and without well-known habits.